THYROID CANCER DETECTION USING HIGH-FIELD MAGNETIC RESONANCE IMAGING - I. G. Frolova; E. L. Choinzonov; E. E. Bober; N. Yu Bystrova; M. R. Mukhamedov; S. A. Velichko (Сибирский онкологический журнал)
Findings of dynamic contrast-enhanced magnetic resonance imaging with the use of the time-signal intensity curve were assessed in patient with thyroid cancer. Diagnostic value of high-field dynamic contrast-enhanced MRI in detection of thyroid cancer was analyzed.